Dr. Thomas Cherian; Father of Cancer Surgery in Kerala - K. Chandramohan (Indian J Surg Oncol, 2014)
Dr. Thomas Cherian (1940–2014) is one of the first surgical oncologists from State of Kerala, India. A humble human being, dexterous surgeon, untiring worker, and a dy- namic personality that was Dr. Thomas Cherian. His vision, hardworking abilities and indomitable spirit were exemplary. He has paved path for the development of surgical oncology in Kerala. This article portrays not only the life of a selfless man, but also the beginning of a new speciality of Surgical Oncology in Kerala.